A relaçao terapeuta-paciente: uma abordagem crítica a partir da religião cristã - Teixeira, José Pedro Lopes (2008)
The general objective of this dissertation is to criticise the actual model of relation between the therapist and the patient , starting from fundamental elements of the Christian Religion in the point of therapeutic view. Via a bibliographic research are made a study of the relation between the therapy and the religion , to search for learning the way to interact , way , what patients and therapists complaines. The research is based on the gospel of Marcos, starting from actual biblical authors like Ekkehard W. Stegemann , Gerd Theissen and John P. Meier. Are considered too the theorical bases of concepts and ideas of thinkers like Juan Luis Segundo, Paul Tillich and Victor Frankl. Coming to the conclusion , that the relation therapist-patient is an important promotion agent for faith/confidence to stimulate the natural resources of cure, perceiving approximations and contrasts between practices of Jesus of Nazareth and a brasilian contemporary therapist